Mechanical and Ballistic Resistance Properties of a Coconut Shell Powder Epoxy Composite (Coex) Subjected to Impact Loads - Mohd Sohaimi, Risby (2009)
An armor design study has been carried out to determine the feasibility of utilizing a coconut shell powder (CSP) reinforced composite as one of the protective component in hard body armor application. Few experimental approaches have been carried out to determine the physical and mechanical properties of coconut shell powder-epoxy composite (COEX). The COEX composite panel bonded with Twaron CT716 fabric as its spall liner (or COMBAT) was also subjected to ballistic tests at several impacting velocity in order to determine the COEX armor ballistic resistance capabilities at certain threat levels. The physical properties of CSP-A (coarse grade) with low aspect ratio of 0.71, bulk density of 0.424 g/cm3 and broad particle size distribution were important factors in the its selection as the best powder type for COEX specimen fabrication. This was due to its potential influences (based from the properties) of increasing the particle-matrix interfacial bonding in the COEX composite system. CSP-B (fine grade) and CSP-C (super fine grade) although possessing higher bulk density which can lead to better compaction, were not chosen due to its higher moisture content and aspect ratio. where these properties is expected to give a weak interfacial bonding for the composite system. These statements was proven in the mechanical testing (tensile, flexural, compression and hardness), where COEX-A (with CSP content of 50%) imparts the highest value in all mechanical properties. It had been found that the tensile, compressive and flexural strength of COEX-A was measured at 17.44 MPa, 100.05 MPa and 194.8 MPa respectively when compared to the other COEX configurations. The Rockwell hardness value for COEX-A was also found to be the highest compared to COEX-B and COEX-C. All these mechanical properties play a significant influence in the ballistic resistance capabilities of the COEX materials Statistical models were developed using 2 level of Full Factorial Design method to predict the armor‟s impact resistance and blunt trauma depth using several parameters which are critical to the fabrication and ballistic testing of the COMBAT armor panel. The models were verified and showed good agreement with the actual laboratory test data. Finally, the for actual ballistic armor test of the COMBAT armor panels were tested according to NIJ Standard 0101.08 with 9 mm Full Metal jacket and 7.52 mm M-16 bullets. It was observed that the imprint patterns on the COEX materials could be identified according to the effectiveness in impact energy dissipation. COMBAT test panels were found to withstand impact equivalent to NIJ Level IIIA using a 9 mm FMJ ammunition but perforated at NIJ Level III of 7.62 mm FMJ bullet impacts. Test results showed that COEX panel do possess shock absorbance characteristics and can be utilized as an armor component in the hard body armor system. Dependency on the numbers of Twaron fabric layers as ballistic reinforcements had been reduced up to 3 times with 170 % improvement on energy absorption capabilities when using COEX composite as the frontal component of the armor.